N-acetilcisteína previne a piora da memória espacial induzida por ácido glutárico e lipopolissacarídio em ratos jovens - Rodrigues, Fernanda Silva (2014)
Glutaric aciduria type I (GA-I) is an inborn error of metabolism (EIM) characterized biochemically by accumulation of glutaric acid (GA). The clinical manifestations are mainly neurological and develop during childhood. Among these changes, there are the seizures and cognitive deficits, which may be precipitated by infectious processes. Although growing evidence supports that inflammation and oxidative damage are both involved in learning impairment, it is not known whether inflammatory and oxidative stress markers facilitate GA-induced memory impairment. From this, the main objective of this study was to investigate the performance of rat pups chronically injected with GA and lipopolysaccharide (LPS) in spatial memory test on Barnes maze. To evaluate antioxidant defenses, cytokines levels, Na+, K+-ATPase activity, and hippocampal volume. Furthermore, we also evaluated wheter N-acetylcysteine (NAC) could improve these behavioral, biochemical or structural changes induced by GA and LPS administration. For this, the rat pups were injected with GA (5umol g of body weight-1, subcutaneously; twice per day; from 5th to 28th day of life), and were supplemented with NAC (150 mg/kg/day; intragastric gavage; for the same period). In order to mimic a severe infection state, LPS (2 mg/kg; E.coli 055 B5) or vehicle (saline 0.9%) was injected intraperitoneally, once per day, from 25th to 28th day of life.Oxidative stress biomarkers, antioxidant activity and hippocampal volume were assessed. In this study, GA caused spatial learning deficit in the Barnes maze, and that LPS potentiated the memory impairment induced by GA in rat pups. In addition, GA and LPS increased proinflammatory cytokine levels (TNF- and IL-1), and the co-administration of these compounds potentiated the increase of IL-1 levels but not TNF- levels in the hippocampus of this animals. Although GA and LPS administration increased TBARS (thiobarbituric acid-reactive substance) content, reduced antioxidant defenses and inhibited Na+,K+-ATPase activity (total and subunit α1), GA and LPS co-administration did not have additive effect on oxidative stress markers and Na+, K+ pump. The hippocampal volume did not change after GA or LPS administration. N-acetylcysteine protected against impairment of spatial learning and increase of cytokines levels induced by GA and LPS. The NAC also protected against deleterious effects induced by GA and LPS, as characterized by inhibition of Na+,K+-ATPase activity (total and subunit α1)and increase of TBARS content, as well as the reduction of antioxidant defenses(non protein thiols and glutathione content, superoxide dismutase and catalase activities).These results suggest that inflammatory and oxidative markers may underlie at least in part of the neuropathology of GA-I in this model. Pharmacological protection with NAC during encephalopatic crises could be considered as an adjuvant therapy to prevent hippocampal dysfunction and the progression of disease in children with GA-I.